Characteristics and Outcomes of Cesarean Section Patients at Ibnu Sina Simpang Empat Hospital - Agus, Muthiah Ramadhani; Ardiles, Ardiles (Andalas Obstetrics And Gynecology Journal, 2025)
Introduction: This study aims to determine the characteristics and outcomes of caesarean section patients. Childbirth with the SC method is carried out on the basis of medical indications from both the mother and fetus, such as placenta previa, abnormal presentation or location of the fetus, and other indications that can endanger the life of the mother and fetus. Method: descriptive observational research with a cross-sectional research design that describes the phenomenon of the variables studied objectively based on time samples, behavioral samples, and incident samples at a certain time through medical records of post-cesarean section patients. Result: The maternal age is mostly low risk (80%), multiparous (68%), length of stay 2±0.5. The most common indications for CS are a history of previous CS (31.14%), PROM (17.89%), CPD (8.61%) and oligohydramnios (5.44%) Conclusion: The incidence of cesarean section delivery at RSI Ibnu Sina Simpang Empat from January 2024 to June 2024 increased in the productive age group and most in multiparas. The average length of stay after cesarean section was in accordance with the ACOG standard, which was less than 48 hours. The importance of post-cesarean section assessment and monitoring to optimize maternal and infant health. Keywords: Cesarean section, characteristic, outcome